2013
DOI: 10.1118/1.4814793
|View full text |Cite
|
Sign up to set email alerts
|

SU‐E‐T‐359: Patients Could (and Should) Be Treated in An Upright Position

Abstract: Purpose: Treating patients in an upright (seated) position has several potential advantages including increased lung volume/reduced respiratory motion (lung patients) giving an improved lung DVH, moving other healthy tissue away from the treatment beams (e.g. breast for Hodgkins lymphoma patients), and improved comfort (H&N patients with excess mucus secretion, patients with compromised lung function, etc.). We report on efforts to develop the tools/techniques to add upright treatments to the modern radiothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Aside from the economical arguments, there have been a small, but growing number of studies indicating a possible therapeutic benefit of upright treatment as well. Upright positioning could provide greater comfort for head&neck patients suffering from increased saliva production (25), and patients suffering orthopnea, dyspnea or dysphagia in supine position (26).…”
Section: Clinical Argumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the economical arguments, there have been a small, but growing number of studies indicating a possible therapeutic benefit of upright treatment as well. Upright positioning could provide greater comfort for head&neck patients suffering from increased saliva production (25), and patients suffering orthopnea, dyspnea or dysphagia in supine position (26).…”
Section: Clinical Argumentsmentioning
confidence: 99%
“…Using an upright MRI scanner, Yang et al ( 28) also demonstrated increased lung volume in upright positioning compared to supine, as well as showing a reduced motion amplitude from respiration. The greater lung volume implies greater distance between target and organs at risk, as well as lower mean lung dose, which has been used to argue for better healthy tissue sparing possibility (25). For particle therapy, the important quantity is the water equivalent thickness, which would not change relevantly with greater air volume in the lungs.…”
Section: Clinical Argumentsmentioning
confidence: 99%
“…Another option which could increase the flexibility of a fixed horizontal beam line substantially is an upright positioning of the patient, which lately gained interest again in the community and by vendors. [39][40][41][42]…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an inclined beam line might increase the cost of the treatment compared to a horizontal beam line. Another option which could increase the flexibility of a fixed horizontal beam line substantially is an upright positioning of the patient, which lately gained interest again in the community and by vendors 39–42 …”
Section: Discussionmentioning
confidence: 99%
“…Research is ongoing to develop a specialized treatment chair for this technique. 40,41 In contrast to previous chairs used for upright treatments, this one is being developed with patient comfort in mind to help minimize motion. Interfraction and intrafraction motions tests using this chair, and other chair designs, are planned to assess patient positioning, reproducibility, and detect any necessary modifications.…”
Section: Discussionmentioning
confidence: 99%